Ketentuan Hukum Mengenai Mangkir dalam Omnibus Law - Febri Jaya; Alvin Lauw (Wajah Hukum, 2021)
The number of existing regulations in Indonesia often has the effect of reducing the effectiveness of implementing laws and regulations due to the overlap between regulations. With the enactment of Act Number 11 of 2020 on Job Creation, many labor regulation have been changed, one of which is related to a specific time work agreement. Therefore, this study aims to conduct a study on change to the provision in the employment agreement for a certain period of time, which certainly affects the rights and obligation between worker and employment, this change must be understood by both worker and employment. Through normative legal research, it can be seen that there are a number of things that need to be discussed in relation to the enactment of Act Number 11 of 2020 on Job Creation. As a result of discussion, this study describes absenteeism and the rights of employment if the worker terminates the employment agreement for a certain period of time before the end of the agreement.